Quality of life assement of riverside communities of Tapajós and Cupari Rivers in Pará. (30th September 2020) - Espinosa, M V; Reis, B; de Oliveira, A; Bertaglia, L; Rodrigues, J; França, J N; Ferrero, M V; Dias, L A; Oliveira, A M; Moreira, A
Abstract: Introduction: Riverside population lack basic sanitation infrastructure and access to healthcare. In addition, locals encounter difficulties in accessing basic health care due to climate variability and fluvial activity which results in tidal distortion and attenuation. Quality of life is a broad concept and its measurement should be useful to identify determining and conditioning factors in health-illness process which would be key to the guidance of health public policy measures in a specific community. This study aims at assessing the quality of life of Tapajós and Cupari riverside communities in Pará, Brazil. Methods: A cross-sectional and descriptive study composed of a group of patients aged 18 and over who have sought care during the volunteer health expedition in the Tapajós and Cupari rivers between mid-July and August 2019. The team of students and professors conducting the survey adopted the WHOQOL-bref questionnaire as a measure of quality of life. The questionnaire consists of 25 questions and 5 domains: physical health, psychological, social relationships, environment, and self-assessment of quality of life. Individual scores vary between 4 and 20. Scores ≤ 10 suggest low quality of life whereas >10 suggest higher quality of life. This statistical analysis was carried out in the SPSS program and was described by means of summary measures: minimum, maximum, median, and standard deviation. Outcomes:The five domains scored >10, with the highest being the psychological domain (16, 48, dp = 1, 71) and the lowest the environment (14, 12 dp = 1, 99). Conclusions: In spite of inherent difficulties generally found in riverside communities, participants reported high perception of quality of life in all domains. The lowest overall perception was the environment domain. This result confirms not only the barriers of physical infrastructure but also access to quality services as a negative health and life determinant. Key messages: Assessing the quality of life is key to determine which factors influence the health-illness process within a community. Assessing the quality of life is fundamental to guide strategies aimed at intervening in social determinants.